Influence of trait empathy on the emotion evoked by sad music and on the preference for it - Kawakami, Ai; Katahira, Kenji (Frontiers in Psychology, 2015)
Some people experience pleasant emotion when listening to sad music. Therefore, they can enjoy listening to it. In the current study, we aimed to investigate such apparently paradoxical emotional mechanisms and focused on the influence of individuals’ trait empathy, which has been reported to associate with emotional responses to sad music and a preference for it. Eighty-four elementary school children (42 males and 42 females, mean age 11.9 years) listened to two kinds of sad music and rated their emotional state and liking towards them. In addition, trait empathy was assessed using the IRI scale, which comprises four sub-components: Empathic Concern, Personal Distress, Perspective Taking, and Fantasy. We conducted a path analysis and tested our proposed model that hypothesized that trait empathy and its sub-components would affect the preference for sad music directly or indirectly, mediated by the emotional response to the sad music. Our findings indicated that fantasy, a sub-component of trait empathy, was directly associated with liking sad music. Additionally, perspective taking ability, another sub-component of trait empathy, was correlated with the emotional response to sad music. Furthermore, the experience of pleasant emotions contributed to liking sad music.